Consumer expectations in the context of unique tourism products - Čivre, Žana (Academica turistica, 2024)
In response to the contemporary trend of tourists actively seeking novel, unique, and distinctive experiences, this study explores the relationship between tourists’ perceptions of the uniqueness of tourism products and their expectations. Spe-cifically, it focuses on the coastal destinations of Piran and Portorož in Slovenia, analysing four unique experiences: Gourmet Olive Tours, Fonda Fish Garden, The Disappearance of Tartini’s Violin, and E-bike Extravaganza Mareatour. Using a qu-antitative approach, the study supports the hypothesis that the perceived uniqu-eness of new tourism products significantly influences tourists’ expectations. The findings support the hypothesis, revealing that the perceived uniqueness of an expe-rience is closely tied to its incorporation of local character and a strong experiential or personal touch. For instance, the Gourmet Olive Tour experience, perceived as the most unique, offers tourists immersive encounters within a landscape park and interactions with a local olive family. Furthermore, the study identifies a hierar-chy of expectations among tourists, ranging from increasing knowledge of the local offer, traditions, and history, to seeking unique activities and having confidence that the experience will meet their expectations. In conclusion, the research underscores that consumers harbour high expectations for unique experiences, underlining the importance of infusing tourism products with experiential and emotional elements. The positive correlation between perceived uniqueness and expectations undersco-res the imperative for crafting distinct and memorable tourism offerings. The study enriches our understanding of the relationship between perceived uniqueness and expectations, offering insights for destination marketers creating distinctive tou-rism products. It also provides recommendations for future research, enhancing scholarly discourse on tourism product development and consumer behaviour.
Keywords: consumer expectations; destination; doživljajski turizem; Piran; Portorož; pričakovanja potrošnikov; tourism experience; turistične destinacije; turistični proizvodi; unique tourism products